Harnessing Stoic Philosophy to Enhance Learning Motivation in the Age of Digital Education - Ansiska, Paisal (INDO PUBLISHING, 2025)
This study examines the influence of applying Stoic philosophy on students' learning motivation and self-discipline in the digital era. Stoicism, which emphasizes self-control and focusing on things that can be controlled, is considered relevant in the context of University, especially in overcoming academic challenges and digital distractions. This research involved 100 students divided into two groups: an experimental group (n=50) that received Stoicism training and a control group (n=50) that did not receive any intervention. The assessed aspects included intrinsic motivation, extrinsic motivation, time management, task completion consistency, and the ability to resist distractions. The results of the study showed that the experimental group experienced significant improvements in all analyzed aspects, with higher average score changes compared to the control group. Regression analysis showed a p-value < 0.001 for most aspects, indicating that the Stoicism intervention had a significant impact on increasing learning motivation and self-discipline. These findings affirm that the application of Stoicism can be an effective approach to enhancing students' academic performance. Therefore, it is recommended that University institutions consider integrating Stoic programs into their curricula or support services to promote students' personal and professional development in the challenging digital era.